Introductory econometrics : using Monte Carlo simulation with Microsoft Excel - Barreto, Humberto, 1960- (Cambridge University Press, 2006)
This highly accessible and innovative textbook comes with a CD with Excel (R) workbooks and add-ins where students actually do econometrics - running Monte Carlo simulations, regressions, and other procedures in the familiar environment of Excel (R). Web site support can be found at www.wabash.edu/econometrics.